A20 Inhibits Tumor Necrosis Factor (TNF) Alpha-Induced Apoptosis by Disrupting Recruitment of TRADD and RIP to the TNF Receptor 1 Complex in Jurkat T Cells - He, Kai-Li (American Society for Microbiology, 2002)
Tumor necrosis factor receptor 1 (TNFR1) can trigger distinct signaling pathways leading to either the activation of NF-κB transcription factors or apoptosis. NF-κB activation results in the expression of antiapoptotic genes that inhibit the apoptosis pathway that is activated in parallel. However, the molecular mechanism of this inhibition remains poorly characterized. We have isolated a Jurkat T-cell mutant that exhibits enhanced sensitivity to TNF-induced apoptosis as a result of a deficiency in I-κB kinase γ (IKKγ)/NEMO, an essential component of the IKK complex and NF-κB pathway. We show here that the zinc finger protein A20 is an NF-κB-inducible gene that can protect the IKKγ-deficient cells from TNF-induced apoptosis by disrupting the recruitment of the death domain signaling molecules TRADD and RIP to the receptor signaling complex. Our study, together with reports on the role of other antiapoptotic proteins such as c-FLIP and c-IAP, suggests that, in order to ensure an effective shutdown of the apoptotic pathway, TNF induces multiple NF-κB-dependent genes that inhibit successive steps in the TNFR1 death signaling pathway.